Measuring psychological need states in sport: Theoretical considerations and a new measure. (March 2020) - Bhavsar, Nikita; Bartholomew, Kimberley J.; Quested, Eleanor; Gucciardi, Daniel F.; Thøgersen-Ntoumani, Cecilie; Reeve, Johnmarshall; Sarrazin, Philippe; Ntoumanis, Nikos
Abstract: Objectives: Research guided by Self-determination Theory (Deci & Ryan, 1985; Ryan & Deci, 2017) has repeatedly demonstrated the importance of focusing on both the bright (satisfaction) and dark (frustration) sides of the three basic psychological needs. Recently, researchers have also argued for the utility of assessing a third need state, that of "unfulfillment". In this paper, we outline an effort to develop and provide initial validity evidence for scores of a new multidimensional and sport-specific measure, the Psychological Need States in Sport-Scale (PNSS-S), to assess the satisfaction, frustration, and unfulfillment of all three needs. Method: In Study 1, we developed 46 candidate items, and tested evidence for the factorial structure of the responses to the newly developed items, internal consistency and discriminant validity of the subscale scores. Following refinement, the replication of the favored model was tested using an independent sample of athletes in Study 2. Evidence for the nomological network of the subscales of the new measure was also demonstrated in Study 2. Results: Factor models incorporating all three need states showed poor fit with the data. However, following post-hoc modifications, a six-factor model assessing the need states of satisfaction and frustration, separately for autonomy, competence, and relatedness, was found to have good fit to the data. After refinement, the 29-item six-factor model was found to demonstrate good fit, good standardized factor loadings, factor correlations in the expected directions, and acceptable estimates of internal consistency in Study 2. Tests of nomological networks showed that the six need states were significantly predicted by contextual autonomy, competence, and relatedness support/thwarts as expected. Autonomy and competence need satisfaction were significantly associated with engagement; and competence and relatedness need satisfaction were significantly associated with positive affect. In addition, autonomy and competence need frustration were significantly associated with exhaustion and all three need frustration states significantly predicted negative affect. Conclusions: A tripartite conceptualization of the need states was not empirically supported. Nevertheless, the PNSS-S makes a unique contribution to the sport literature, as it represents the first sport-specific measure of six distinct, yet, correlated states of the satisfaction and frustration of autonomy, competence, and relatedness needs. Highlights: Psychological need states proposed to comprise satisfaction, frustration, and unfulfillment. An attempt to develop a new tripartite measure of athlete need states was described. No empirical support was found for a tripartite conceptualisation of need states. Lack of evidence for need unfulfillment as the third need state is discussed. Development and initial validation of a measure of the satisfaction and frustration of athletes' three needs is presented.